Strategies and interventions to strengthen pharmacovigilance systems in low-income and middle-income countries: a scoping review - Andrea Kuemmerle; Christian Burri; Olga Menang; Karen Maigetter (BMJ Open, 2023)
Objectives The slow progress of pharmacovigilance (PV) in low-income and middle-income countries (LMIC) raises questions about core challenges on the growth of PV, and the appropriateness of strategies used so far to develop PV. Therefore, this scoping review aims to describe strategies and interventions to strengthen PV in LMIC and to propose recommendations for future investments in PV capacity building.Inclusion criteria Publications included were primary studies, articles, policy and guideline papers, describing interventions to strengthen PV in LMIC.Methods The review was conducted following the Joanna Briggs Institute (JBI) guidelines on conducting scoping reviews. Literature searches were performed in MEDLINE, EMBASE, Web of Science, PDQ-evidence, CINAHL and other relevant websites from January 1990 to January 2021. Two reviewers independently screened titles, abstracts and full texts. One reviewer performed data extraction and descriptive analysis, which were reviewed by two other reviewers.Results 10 922 unique titles were screened and 152 were eligible for full text review. Of these, 57 and an additional 13 reports from grey literature fulfilled eligibility criteria for inclusion in the review. These were grouped into two categories: (1) Interventions aimed at increasing PV knowledge and adverse drug reactions (ADR) reporting (45 papers), primarily education of healthcare professionals (HCP), alone or in combination with other interventions such as mobile and electronic reporting and (2) Interventions aimed at strengthening various components of the national PV system (25 papers), describing strategies or mixed interventions implemented at the national level, targeting different components of the national PV system.Conclusions Results of this review suggest that educating HCP on ADR reporting is the most common approach to build PV capacity in LMIC. Though important, education alone is insufficient and should ideally be organised within the holistic framework of strengthening national PV systems, with a focus on also building capacity for advanced activities such as signal detection.